White House Seeks Wide Smoking Ban - Chen-E (Tufts Archival Research Center, 2007)
Incomplete; Two segments of articles from the Washington Times (3/20/1994) on proposed smoking ban: "White House Seeks Wide Smoking Ban" and "Tobacco Industry Fights Spiraling Efforts to Snuff It Out". First piece discusses Clinton administration proposal to ban all indoor smoking in workplaces. Second piece discusses "hostile climate" surrounding tobacco and cigarettes and industry efforts to combat it. Quotes Walker Merryman , as well as Congressman Waxman on hypothesized reasons. Analyzes smoking bans in states, cities, and fast food chains, and comments that federal support is surprising. Includes discussion of EPA report on environmental tobacco smoke as a carcinogen and attempts at FDA regulation. Claims "steamroller" has been building for years.